Foreign Policy Behaviour: Capabilities as Determinant in Nigeria’s Leadership Role in Africa - Ayodeji Adeleke, Adewole (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Critically looking at the capabilities of Nigeria in relation to West Africa and the rest of the continent in general gives one a better understanding of the country’s foreign policy behaviour. Substantial changes started to occur in Nigeria’s capabilities in the 1970s, especially in the areas of economic, military, diplomatic and institutional resources when compared with the rest of Africa. In a complex manner during this period, contests for leadership at regional and continental levels were tied to differences in national capabilities and ideological resources. However, Nigeria’s role at creating ECOWAS in 1975 validated the connectivity between economic capabilities and leadership. Also, the limited impact of the international community in Africa since the end of the Cold War conferred on Nigeria more pivotal leadership role on the continent. These have affected the foreign policy behaviour of Nigeria not only in Africa but the world over. The paper seeks to examine Nigeria’s capabilities in relation to some leading African nations. The study adopts descriptive and analytical approaches and submits that Nigeria’s leadership role in Africa has remained constant despite the economic downturn the country is presently facing and it is projected to lead the continent for a long time to come.